2009
DOI: 10.1208/s12248-009-9087-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physiological Intestinal Water in Oral Absorption

Abstract: Abstract. Water volume has impact when the compound has low aqueous solubility. For example, the absorption of compounds with a Biopharmaceutics Classification System class 2 or 4 is likely to be solubility-limited. Provided the formulation does not contribute to a dissolution-limited condition (e.g., particle size, Waterman and Sutton, J Control Release 86: [293][294][295][296][297][298][299][300][301][302][303][304] 2003) and permeability is rapid, any impact on solubility factors in the gastrointestinal (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 26 publications
5
48
0
Order By: Relevance
“…Based on the comparison of the observed and predicted PK for the phase I studies, it was observed that the GastroPlus™ setting of 15% fluid volume in the small intestine best captured the PK profiles, especially C max at doses of 200 mg and above. While in our experience, this adjustment is not always needed, this change in the intestinal fluid volume has been previously reported in the literature (25) and facilitated a better simulation of compound C data. Based on these outcomes, the subsequent simulations of the impact of the API particle size were conducted using 15% intestinal fluid volume.…”
Section: Software Usedsupporting
confidence: 52%
“…Based on the comparison of the observed and predicted PK for the phase I studies, it was observed that the GastroPlus™ setting of 15% fluid volume in the small intestine best captured the PK profiles, especially C max at doses of 200 mg and above. While in our experience, this adjustment is not always needed, this change in the intestinal fluid volume has been previously reported in the literature (25) and facilitated a better simulation of compound C data. Based on these outcomes, the subsequent simulations of the impact of the API particle size were conducted using 15% intestinal fluid volume.…”
Section: Software Usedsupporting
confidence: 52%
“…BCS class 2 and 4 drugs. For those drugs, accounting for the GI physiological factors affecting the solubility, dissolution and precipitation along the GI tract is absolutely necessary, especially when it comes to the prediction and understanding of their regional intestinal absorption (4,25,(83)(84)(85). However, for our simulations, that assumption seemed reasonable as the majority of the drugs listed in Table II can be classified as highly soluble (BCS classes 1 and 3), with the exception of furosemide, which is poorly soluble weak acid (pKa=3.9), yet its solubility is expected to be high at the intestinal pH range (6-7.4) (85,86).…”
Section: Discussionmentioning
confidence: 99%
“…8, 9a, 9b, 12a, and 12b for three drug constructs in a patient described by average physiological parameters. The value for small intestinal fluid volume (V l ) is 70 mL and the transit time (T l r) is 180 min, which represent median values from the literature (22,37,(44)(45)(46). The plateau concentration (C g p) was set to 10 μg/mL to reflect the low solubility values for many BCS II compounds, particularly those for which dissolution enhancement strategies, such as amorphization, are sought.…”
Section: Methodsmentioning
confidence: 99%
“…Using USP Apparatus (type 1 or 2), the volume ranges from 250 mL to 1 L (32), while the volume of the small intestinal fluid has been reported to be only 45 to 320 mL (37). The lower in vivo volume can result in a significantly lower amount of drug in solution in vivo (22). This is particularly important for amorphous formulations where the degree of supersaturation and excess remaining solid can influence the time course of precipitation (3).…”
Section: Relationship Between In Vitro Drug Concentration Profile Andmentioning
confidence: 99%
See 1 more Smart Citation